Effects of feeding different postbiotics produced by Lactobacillus plantarum on growth performance, carcass yield, intestinal morphology, gut microbiota composition, immune status, and growth gene expression in broilers under heat stress - Merzza, Humam Ali; Loh, Teck Chwen; Foo, Hooi Ling; Samsudin, Anjas Asmara @ Ab Hadi; Mohamed Mustapha, Noordin; Idrus, Zulkifli; Wan Ibrahim, Wan Ahmad Izuddin (MDPI, 2019)
The effects of feeding different postbiotics on growth performance, carcass yield, intestinal morphology, gut microbiota, immune status, and growth hormone receptor (GHR) and insulin-like growth factor 1 (IGF-1) gene expression in broilers under heat stress were assessed in this study. A total of 252 one-day-old male broiler chicks (Cobb 500) were randomly assigned in cages in identical environmentally controlled chambers. During the starter period from 1 to 21 days, all the birds were fed the same basal diet. On day 22, the birds were weighed and randomly divided into six treatment groups and exposed to cyclic high temperature at 36 ± 1 °C for 3 h per day from 11:00 to 14:00 until the end of the experiment. From day 22 to 42 (finisher period), an equal number of birds were subjected to one of the following diets: NC (negative control) basal diet; PC (positive control) basal diet + 0.02% oxytetracycline; or AA (ascorbic acid) basal diet + 0.02% ascorbic acid. The other three groups (RI11, RS5 and UL4) were basal diet + 0.3% different postbiotics (produced from different Lactobacillus plantarum strains, and defined as RI11, RS5 and UL4, respectively). The results demonstrated that birds fed RI11 diets had significantly higher final body weight, total weight gain and average daily gain than the birds that received the NC, PC and AA treatments. The feed conversion ratio was significantly higher in the RI11 group compared with the other groups. Carcass parameters were not affected by the postbiotic-supplemented diet. Postbiotic supplementation improved villi height significantly in the duodenum, jejunum and ileum compared to the NC, PC and AA treatments. The crypt depth of the duodenum and ileum was significantly higher in NC group compared to other treatment groups except RI11 in duodenum, and UL4 in ileum was not different with NC groups. The villus height to crypt depth ratio of duodenum and ileum was significantly higher for the postbiotic treatment groups and AA than the PC and NC treatment groups. The postbiotic RI11 group recorded significantly higher caecum total bacteria and Lactobacillus count and lower Salmonella count compared to the NC and PC treatment groups. The Bifidobacterium population in the NC group was significantly lower compared to the other treatment groups. The postbiotic (RI11, RS5 and UL4) and AA treatment groups showed lower Enterobacteriaceae and E. coli counts and caecal pH than the NC and PC treatment groups. The plasma immunoglobulin M (IgM) level was significantly higher in the birds receiving postbiotic RI11 than those receiving other treatments. The plasma immunoglobulin G (IgG) level was higher in the RI11 treatment group than in the NC, AA and RS5 groups. The plasma immunoglobulin A (IgA) level was not affected by postbiotic supplements. The hepatic GHR mRNA expression level was significantly increased in birds fed postbiotics RI11, RS5 and UL4, AA and PC compared to the NC-fed birds. Postbiotic RI11 led to significantly higher hepatic IGF-1 mRNA expression level compared to the NC, PC, and AA treatments. Mortality was numerically lesser in the postbiotic treatment groups, but not significantly different among all the treatments. In conclusion, among the postbiotics applied in the current study as compared with NC, PC and AA, RI11 could be used as a potential alternative antibiotic growth promoter and anti-stress treatment in the poultry industry.